AWARENESS, ATTITUDE AND PRACTICES OF PRE-MARITAL GENOTYPE TEST AMONG UN-MARRIED STUDENTS OF THE POLYTECHNIC, IBADAN, NIGERIA (2014)
Sickle Cell Anaemia (SCA) is one of the major causes of morbidity and mortality and a strategic way of reducing the problem is to educate the public and create more awareness on its causes and prevention. There is need for adequate information on awareness and attitude of young adults in tertiary institutions to undertake Pre-marital Genotype Test (PGT).Therefore, this study was aimed at determining the awareness, attitude, and practices of PGT among unmarried students of The Polytechnic, Ibadan. A cross sectional survey was conducted among 382 students who were randomly selected from the four halls of residence in The Polytechnic Ibadan, using a multistage sampling technique. A semi-structured questionnaire which included information on socio-demographic characteristics, awareness about SCA and PGT, 40- point attitude scale relating to PGT, practice of PGT and intention to undertake the test was administered on the respondents. Scores of < 20 and ≥ 20 were classified as negative and positive respectively. Descriptive statistics and Chi-square test were used to analyse the data with level of significance set at 5%. The mean age of respondents was 21.6 ± 3.1 years, 56.6% were females, 68.6% were Christians and 35.5% were in their first year of the National Diploma (ND) course. Respondents’ awareness of SCA and PGT were 89.0% and 92.3% respectively. Major sources of information on SCA and PGT were television (67.9% and 59.8%), friends (54.9% and 50.6%), parents (44.1% and 59.8%) and health workers (47.4% and 50.3%) for both sexes. More than half of the respondents (58.4%) knew their Haemoglobin (Hb) genotype. Of those that claimed to know their Haemoglobin (Hb) genotype, 37.3%, 17.1%, 3.1% and 0.9% were AA, AS, SS and AC respectively. Parents were the major decision makers for respective Hb genotype testing. Of those that knew their Hb genotype, 18.2% and 26.2% of males and females respectively had informed their partners of the result. In respect to respondent’s attitude to PGT, 54.0% had positive and 46.0% had negative attitude. Less than quarter (23.4%) of the respondents would not marry anyone with SCA, 58.4% agreed that it should not be a hindrance to marriage, while 55.4% affirmed their right to know their partner’s genotype before marriage and 37.3% reported that their partner’s genotype result would affect their selection of spouse. Furthermore, majority (85.3%) knew the importance of PGT. About 35.0% of those who did not know their Hb genotype intend to undertake the test before marriage. There was significant relationship between respondent’s awareness about SCA and awareness about genotype testing (p= 0.001). Awareness and practice in respect to sickle cell anaemia and pre-marital genotype test among respondents were high. Partner’s result affects the decision of respondents especially those with positive attitude towards premarital genotype test as critical factor. More awareness programmes should be created by the stakeholders during fresher’s orientation programme by educating the students on premarital genotype test and the consequences of actions guiding their choice of partner.